Innovative clinical trial design for pediatric therapeutics. Issue 5 (September 2011) - Laughon, Matthew M; Benjamin, Daniel K; Capparelli, Edmund V; Kearns, Gregory L; Berezny, Katherine; Paul, Ian M; Wade, Kelly; Barrett, Jeff; Smith, Phillip Brian; Cohen-Wolkowiez, Michael
Until approximately 15 years ago, sponsors rarely included children in the development of therapeutics. US and European legislation has resulted in an increase in the number of pediatric trials and specific label changes and dosing recommendations, although infants remain an understudied group. The lack of clinical trials in children is partly due to specific challenges in conducting trials in this patient population. Therapeutics in special populations, including premature infants, obese children and children receiving extracorporeal life support, are even less studied. National research networks in Europe and the USA are beginning to address some of the gaps in pediatric therapeutics using novel clinical trial designs. Recent innovations in pediatric clinical trial design, including sparse and scavenged sampling, population pharmacokinetic analyses and 'opportunistic'' studies, have addressed some of the historical challenges associated with clinical trials in children.